2022
DOI: 10.1371/journal.pone.0279580
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and its associated factors among epileptic patients at Dessie Comprehensive Specialized Hospital, Northeast Ethiopia; a hospital-based comparative cross-sectional study

Abstract: Introduction Metabolic syndrome is a group of metabolic risk factors which are associated with an increased risk of cardiovascular disease and type2 diabetes. Nowadays, several studies have shown that the burden of metabolic syndrome is increasing among epileptic patients, and leads to MS-associated complications, including cardiovascular disease. However, getting published documents has been limited in Ethiopia and the study area. Therefore, we aimed to analyze the magnitude and associated factors of metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…VPA suppresses the gene expression of adiponectin in mature adipocytes, leading to hypoadiponectinemia, which is strongly linked to weight gain and insulin resistance [8,9,10]. The literature also mentions involvement of the hypothalamus, whether through damage to the nuclei themselves by epileptic seizures and the resulting imbalance between energy intake and consumption, or excessive activation of the hypothalamus-pituitary-adrenal axis [4].…”
Section: Metabolic Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation

Metabolic Syndrome in Patients With Epilepsy

Petelin Gadže,
Hodžić,
Đapić Ivančić
et al. 2024
Preprint
“…VPA suppresses the gene expression of adiponectin in mature adipocytes, leading to hypoadiponectinemia, which is strongly linked to weight gain and insulin resistance [8,9,10]. The literature also mentions involvement of the hypothalamus, whether through damage to the nuclei themselves by epileptic seizures and the resulting imbalance between energy intake and consumption, or excessive activation of the hypothalamus-pituitary-adrenal axis [4].…”
Section: Metabolic Disturbancesmentioning
confidence: 99%
“…In a study conducted by Nair et al, nearly one-third of adults under 50 years old with epilepsy who were undergoing antiepileptic therapy had MetS [3]. Beyene-Kassaw and colleagues conducted a cross-sectional study and found that the prevalence of MetS, based on the NCEP ATP III definition, was 25.5% in adult PWE, compared to 13.7% in the control group [4]. Ndayambaje and colleagues studied 1,076 adult epilepsy patients using AEDs and found a prevalence rate of 30.6%, with the highest rate observed in the 46-60 age group [5].…”
Section: Introductionmentioning
confidence: 99%

Metabolic Syndrome in Patients With Epilepsy

Petelin Gadže,
Hodžić,
Đapić Ivančić
et al. 2024
Preprint
“…Subjects with MetS mainly present with abdominal obesity, hyperglycemia, hypertension, and dyslipidemia ( 2 ). It was also closely associated with a higher cardiovascular disease (CVD) risk, type 2 diabetes (T2D) risk, and overall mortality ( 3 , 4 ). MetS results from complicated risk factors interaction among genetic, metabolic, diet, lifestyle, and environmental factors ( 5 ).…”
Section: Introductionmentioning
confidence: 99%